International and Macroeconomic Determinants of Oil Price: Evidence from Gulf Cooperation Council Countries - Albaity, Mohamed; Mustafa, Hasan (International Journal of Energy Economics and Policy, 2018)
This study investigates the long- and short-run relationships between oil prices and stock market returns, exchange rates, gold prices, and linear and non-linear output, for the six Gulf Cooperation Council (GCC) countries. The study performs a panel and time-series cointegration and causality analysis based on monthly data from 2005 to 2015. The results indicate co-movement among these variables in the long run. The causality test shows a one-way relationship between oil prices and GDP, and a two-way relationship between stock returns and oil prices. For robustness, the sample was divided into two sub-periods: before and after the 2007/2008 global financial crisis. A long-run relationship was found among the variables, but there was no short-run relationship between the variables and oil prices before the crisis. Oil shocks had a significant impact on gold returns and exchange rate growth, while the GDP growth rate affected oil prices. The individual countries' results suggest the presence of a long-run relationship as well as short-run dynamics between selected variables and oil price for a majority of the GCC countries. These results suggest the need for policies aimed at further reducing dependence on oil, since the effect of oil shocks is still significant in these economies. Keywords: Oil price; macroeconomic dynamics; panel cointegration; Dumitrescu-Hurlin panel causality test, Gulf Cooperation Council. JEL Classifications: C23, E31, Q30, Q31, Q35